2003
DOI: 10.2320/matertrans.44.2375
|View full text |Cite
|
Sign up to set email alerts
|

Sn-Ag Based Solders Bonded to Ni-P/Au Plating: Effects of Interfacial Structure on Joint Strength

Abstract: This study investigates interfacial reaction and joint strength of Sn-Ag and Sn-Ag-Cu solder balls bonded to electroless Ni-P plating with various thicknesses of Au coating (50, 250 and 500 nm). For the Sn-Ag solder joints, a P-rich layer formed after reflow-soldering at the joint interface, regardless of thickness of the Au coating. However, for the Sn-Ag-Cu solder joints, a P-rich layer formed at the joint interface only in those samples with Au coating of 250 and 500 nm. Fractures were found to occur at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, due to the barrier effect of this layer against the diffusion of Ni to solder, formation of intermetallic compound at inside of Sn-Ag solder was not occur as such even if holding time of peak temperature was extended. 4,5) While, in this Ni/Sn-Ag/Au/Ni-20Co joint, much intermetallic compounds were formed and the amount of the heat of melting decreased. The microstructure of specimen in the case of heating until 553 K was similar to that in the case of holding at 513 K for 1:8 Â 10 3 s, moreover, the endothermic peak decreased in the case of heating at Exo.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the barrier effect of this layer against the diffusion of Ni to solder, formation of intermetallic compound at inside of Sn-Ag solder was not occur as such even if holding time of peak temperature was extended. 4,5) While, in this Ni/Sn-Ag/Au/Ni-20Co joint, much intermetallic compounds were formed and the amount of the heat of melting decreased. The microstructure of specimen in the case of heating until 553 K was similar to that in the case of holding at 513 K for 1:8 Â 10 3 s, moreover, the endothermic peak decreased in the case of heating at Exo.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of failure mechanisms in other kinds of tests, like pull or shear tests, have shown that the failure mechanism is strongly dependent on the test method, the geometry of the solder joint, and the temperature. [9][10][11][12][13][14][15] In general, the fracture behavior can be sorted out to occur either as a ductile fracture in the bulk solder, as a brittle fracture along the intermetallic layer, or as a combination of these two fracture modes. In the shear test, the fracture usually occurs in the bulk solder, but thermal aging may cause the fracture to occur in a more brittle manner in joints on Cu.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reaction between solders and Cu/Ni-P/Au metallization causes some problems in the reliability of solder joints. It has been reported that a brittle intermetallic compound layer and/or P-rich layer formed at the interface between solder and Ni-P plating resulted in degradation of the joint properties [4][5][6][7][8]. Moreover, a thick Au coating may cause degradation in the joint reliability [9][10].…”
Section: Introductionmentioning
confidence: 99%